If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4=4(1-4x)+8(x-4)
We simplify the equation to the form, which is simple to understand
4=4(1-4x)+8(x-4)
Reorder the terms in parentheses
4=+(+4-16x)+8*(x-4)
Remove unnecessary parentheses
+4=+4-16x+8+*(+x-4+)
Reorder the terms in parentheses
4=+4-16x+(+8x-32)
Remove unnecessary parentheses
+4=+4-16x+8x-32
We move all terms containing x to the left and all other terms to the right.
+16x-8x=+4-32-4
We simplify left and right side of the equation.
+8x=-32
We divide both sides of the equation by 8 to get x.
x=-4
| 3[-4-(-4+5)]= | | 3(y-8)=-y | | 7x(6x-2)=180 | | 4x=3y-7-2x | | 16y-8-8y=27 | | 10.2a+3.9=32a | | -5+h=-34 | | -4m(-7n)+(3d)(-4c)= | | 5x^2+3x-6=0 | | 4088=x(56) | | .5+.4= | | 8x+2(12x+6)= | | x+(2x-30)=150 | | 5-(5.25+3.1x)=-6.2(2.5x+1.9) | | 5(y-1)=13-y | | 2m^2-9m-35=0 | | 6(x+5)=-36 | | 4x-5(x+3)=23 | | 25-(x+7)=6x-3 | | 8-4x=-2x-4 | | 3(15x+5)-15=3(15x-15)+3 | | 9-(4+5)= | | -2x-4(-2x-2)=-10 | | 15(8-3)-64=x | | 6x+4=4x+26 | | -4x-7+6x=-6 | | 5a-2c+7=(6a-3c+2) | | -6(a+9)=-24+4a | | -6-x=-3x-2 | | p=21 | | -3-2p=-3(p+2) | | 9(y-1)=11-y |